Readjusting the EU’s regulation of text and data mining in the age of artificial intelligence - Manteghi, Maryna (fi=Turun yliopisto|en=University of Turku|, 2025)
This doctoral dissertation examines whether the EU’s current regulation of text and data mining (TDM) adequately considers the interests and implications related to technological developments and the fundamental freedoms of research and information. The study establishes three key aspects for discussion: first, it analyses how copyright and the sui generis database right may restrict the use of TDM in the EU; second, it explores the reasons for adopting specific TDM exceptions, and how the situation has evolved following the introduction of Articles 3 and 4 of Directive (EU) 2019/790 on Copyright and Related Rights in the Digital Single Market; and third, it identifies the most effective ways to improve the current EU regulation of TDM. The dissertation consists of this summary and four substudies. The first article provides background on the topic and analyses potential improvements to the scope of TDM exceptions during their national transpositions. The second substudy examines the legal framework governing TDM from the perspective of fundamental rights and freedoms. The third publication reviews Article 35 of the proposed Data Act as an alternative mechanism for researchers. Lastly, the fourth article addresses the growing copyright-related concerns arising from the training of generative AI systems and explores potential solutions. The findings of this dissertation emphasise the need to readjust the current EU regulation of TDM to ensure that it keeps pace with the rapid development of AI while remaining aligned with fundamental constitutional values. Accordingly, the research proposes changes to TDM exceptions aimed at establishing a long-lasting balance between the rights and interests of rightholders and those of TDM users.

--- Tämä väitöskirja tarkastelee, ottaako Euroopan unionin nykyinen tekstin- ja tiedonlouhintaa (TDM) koskeva sääntely riittävästi huomioon teknologiseen kehitykseen sekä tutkimuksen ja tiedonsaannin perusvapauksiin liittyvät intressit ja vaikutukset. Tutkimus rakentuu kolmeen keskeiseen näkökulmaan: ensinnäkin se analysoi, miten tekijänoikeus ja sui generis -tietokantaoikeus voivat rajoittaa TDM:n käyttöä Euroopan unionissa; toiseksi se tarkastelee syitä TDM-poikkeusten säätämiselle sekä sitä, miten tilanne on kehittynyt Euroopan parlamentin ja neuvoston direktiivin (EU) 2019/790 tekijänoikeudesta ja lähioikeuksista digitaalisilla sisämarkkinoilla 3 ja 4 artiklan käyttöönoton jälkeen; ja kolmanneksi se tunnistaa tehokkaimmat keinot nykyisen EU:n TDM-sääntelyn parantamiseksi. Väitöskirja koostuu tästä yhteenvedosta ja neljästä osatutkimuksesta. Ensimmäinen artikkeli tarjoaa aiheeseen liittyvän taustan ja analysoi mahdollisia parannuksia TDM-poikkeusten soveltamisalaan niiden kansallisen täytäntöönpanon yhteydessä. Toinen osatutkimus tarkastelee TDM:ää koskevaa oikeudellista kehystä perusoikeuksien ja -vapauksien näkökulmasta. Kolmas julkaisu arvioi ehdotetun data-asetuksen 35 artiklaa vaihtoehtoisena mekanismina tutkijoille. Viimeinen artikkeli käsittelee generatiivisten tekoälyjärjestelmien kouluttamiseen liittyviä tekijänoikeudellisia huolia ja tarkastelee mahdollisia ratkaisuja. Väitöskirjan tulokset korostavat tarvetta tarkistaa ja ajanmukaistaa EU:n nykyistä TDM-sääntelyä siten, että se pysyy tekoälyn nopean kehityksen tahdissa ja säilyttää samalla yhteyden keskeisiin perustuslaillisiin arvoihin. Tutkimus ehdottaa muutoksia TDM-poikkeuksiin tavoitteenaan saavuttaa kestävä tasapaino oikeudenhaltijoiden ja TDM:n käyttäjien oikeuksien ja etujen välillä.